Hubungan Support System Keluarga dengan Tingkat Kecemasan Anak Prasekolah yang Dirawat DI RSUD Dr. Moewardi Surakarta - Irdawati,; Wibowo, Thomas Ari (Jurusan Keperawatan FIKES UNSOED, 2010)
Anxiety is a situation that is not fun, and it can happen to everyone, including preschoolers. One of the negative effects of anxiety may lower the immune system that affect the healing process of children who are undergoing treatment. To cope with anxiety in children, it needs a good support, ie family support. The purpose of this study was to determine the relationships family support system to the level of anxiety in preschool children who are hospitalized in the ward Melati 2 Hospital Dr. Moewardi Surakarta. This was descriptive correlative study to analyze the relationship between family support system with a level of anxiety in preschool children who were treated in hospitals Dr. Moewardi Surakarta. Study sample were 30 preschool children who are hospitalized in the ward Melati 2 Hospital Dr. Moewardi Surakarta. The methods of data retrieval was convenience sampling. Data processing techniques used Spearman Rank analysis techniques. The study concluded, the majority of respondents gave a good family support at 83.3%. Most preschoolers are admitted to the ward boy Melati 2 Hospital Dr. Moewardi Surakarta has the anxiety level was at 63.3%. There was a family support system relationships with anxiety levels preschool children who are hospitalized in the infirmary wards child Melati 2 Hospital Dr. Moewardi Surakarta.